Analisis Pengaruh Kualitas Produk, Harga dan Lokasi terhadap Keputusan Pembelian Es Teler di UMKM Rumah Es Teler Simpang Lima Gumul Kediri - Nabela Batriska Dewi; Rony Kurniawan (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2025)
This study aims to analyze the effect of product quality, price, and location on purchasing decisions of es teler at Rumah Es Teler MSME located in Simpang Lima Gumul, Kediri. The research employed a quantitative approach with an explanatory survey design. Data were collected through likert-scale questionnaires distributed to 40 respondents who were customers of Rumah Es Teler, selected using purposive sampling with criteria of being at least 17 years old and having made at least one purchase. The data were analyzed using multiple linear regression with SPSS version 25. The results indicate that product quality, price, and location have a positive and significant effect on purchasing decisions, both partially and simultaneously. The Adjusted R Square value of 0.915 indicates that the independent variables explain 91.5% of the variance in purchasing decisions. These findings suggest that purchasing decisions for es teler are shaped by the combined influence of high product quality, appropriate pricing, and a strategic business location.